2015
DOI: 10.1260/0263-0923.34.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Annoyance Due to Vibrations in Dwellings Generated from Ground Transportation: A Review

Abstract: Over the past decades, the improvement of the quality of buildings regarding sound insulation has made it possible to reduce noise exposure. But this improvement has led to the increasing importance of other environmental nuisances such as vibrations. Just like noise, vibrations can also affect human health and well-being. National authorities are progressively becoming aware of the adverse effects of vibrations on human beings. One of these adverse effects is vibration annoyance. As a prerequisite for studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…This study provides further support to the statement in the review by Trolle et al 2015 [71] that typical vibration weighting used in standards (e.g., Wm) do not provide sufficient protection under certain circumstances. Furthermore, the required time weighting "slow" in the Austrian standard can lead to a slight underestimation of the exposure peaks at the perceptual level.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study provides further support to the statement in the review by Trolle et al 2015 [71] that typical vibration weighting used in standards (e.g., Wm) do not provide sufficient protection under certain circumstances. Furthermore, the required time weighting "slow" in the Austrian standard can lead to a slight underestimation of the exposure peaks at the perceptual level.…”
Section: Discussionsupporting
confidence: 86%
“…A recent review [71] concluded, that commonly used weighting curves (e.g., Wm in Austria) do not correctly reflect annoyance caused by vibrations with multiple frequency components. Furthermore, recent evidence from exposure response curves [72,73] suggest that the standards (e.g., [74] or [48]) may underestimate the potential effects on sleep during evening and night hours".…”
Section: Discussionmentioning
confidence: 99%
“…In the recent decades population in the cities has grown. Exposure to vibrations from environmental sources like railways, tramways or roads causes such disturbance like annoyance, sleeping problems or headaches [1][2][3]. Designers and structural engineers focused mainly on dynamical influence of transport systems on structures [4][5][6].…”
Section: Influence Of Location Of Measurement Point On Evaluation Of mentioning
confidence: 99%
“…This is due to the need to design, among others, barriers in the ground that limit the transmission of vibrations to building structures or special, expensive vibroisolation. However, if the level of vibration comfort that is specified in the standard is exceeded, it may pose a problem for human health [21,22]. In such cases, it may lead to an uneven influence of vibrations on the internal organs of the human being and, as a consequence, the occurrence of patients that are for example connected with the circulatory system and metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%